Geochemical properties in surface sediments of the Helgoland Mud Area and surrounding sandy areas taken during HEINCKE cruise HE595 in the North Sea - Bingbing Wei; Moritz Holtappels (PANGAEA, 2025)
In March 2022, 56 surface sediments were collected from the Helgoland Mud Area and surrounding sandy areas in the North Sea. These surface sediments were analyzed for grain size, organic carbon (OC) content, total nitrogen content (TN), stable carbon isotope of OC, and abundances of source-specific alkanes and fatty acids, in aim to determine and quantify composition and sources of OC, to understand the degradation and sequestration of marine and terrestrial OC in sediments, and to estimate the burial fluxes and burial efficiencies of marine and terrestrial OC in the Helgoland Mud Area. Detailed dataset interpretation can be found in Wei et al. (2024, in preparation).